2017
DOI: 10.1186/s40479-017-0071-7
|View full text |Cite
|
Sign up to set email alerts
|

Frontal EEG asymmetry in borderline personality disorder is associated with alexithymia

Abstract: BackgroundFrontal EEG asymmetry is a widely studied correlate of emotion processing and psychopathology. Recent research suggests that frontal EEG asymmetry during resting state is related to approach/withdrawal motivation and is also found in affective disorders such as major depressive disorder. Patients with borderline personality disorder (BPD) show aberrant behavior in relation to both approach and withdrawal motivation, which may arguably be associated with their difficulties in emotion processing. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In fact, altered frontal activity was frequently reported in BPD (for review see [52]). In addition, in a previous study of our group, we found that altered frontal asymmetry was related to alexithymia in patients with BPD [3]. In line with these findings, HEP amplitudes over frontal electrodes correlated with alexithymia, but not with dissociative symptoms, the severity of borderline symptoms or childhood trauma.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In fact, altered frontal activity was frequently reported in BPD (for review see [52]). In addition, in a previous study of our group, we found that altered frontal asymmetry was related to alexithymia in patients with BPD [3]. In line with these findings, HEP amplitudes over frontal electrodes correlated with alexithymia, but not with dissociative symptoms, the severity of borderline symptoms or childhood trauma.…”
Section: Discussionsupporting
confidence: 89%
“…Borderline personality disorder (BPD) is characterized by self-injurious and risk-taking behavior, deficits in emotion regulation and poor impulse control, fragile selfimages, unstable relationships and intensive fear of being abandoned [1]. Moreover, many patients with BPD have difficulties in identifying and describing their own feelings, referred to as alexithymia [2][3][4][5]. BPD is also frequently associated with trauma-related dissociative symptoms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, PET studies have associated several BPD traits with altered glucose metabolism in the amygdala [63] and frontal lobe [64]. Furthermore, altered frontal EEG signals are associated with childhood trauma, dissociative symptoms [65] and impaired emotional processing in patients with BPD [66]. Taken together, concurring evidence derived from various biological techniques, including fNIRS, support a biological model of BPD [67].…”
Section: Discussionmentioning
confidence: 81%
“…Traits that could not be unambiguously allocated to any of the categories were excluded (e.g. trait reassurance seeking, Minnix et al, ; trait alexithymia, Flasbeck, Popkirov, & Brüne, ; emotional intelligence, Mikolajczak et al, ; and trait communication apprehension, Beatty et al, ). Furthermore, we also excluded studies reporting only depression given that commonly used instruments to assess depression (e.g.…”
Section: Methodsmentioning
confidence: 99%